Validation of shale brittleness index calculation from wireline log of well BETRO-001 by using XRD test results and uniaxial test as parameters for determining potential of shale hydrocarbon - brown shale of Pematang Group Formation, Central Sumatra Basin, Bengkalis Trough. (December 2018) - Buntoro, A; Prasetyadi, C; Wibowo, R A; Suranto,; Lukmana, A H
Abstract: The parameter of the shale brittleness index is the key to success in hydrocarbon shale stimulation, as in Barnett Shale, Texas, USA, where brittleness is controlled by quartz content. Based on the mineral content of the shale, the ductility (opposite of brittleness) is controlled by the content of clay and calcite. The Brittleness index determines the value of ductile and brittle a rock formation, based on its mineral content. Brittleness of hydrocarbon shale, needed for initiation and propagation of hydraulic fracturing and fracture re-opening. Shale fractability can be evaluated based on geomechanical and mineralogical evaluations for optimization of stimulation planning. Laboratory tests on shale samples from the Brown Shale Formation, Pematang Group in the Central Sumatra Basin, were carried out to obtain elastic properties of rocks, such as Young's Modulus, Poisson's ratio, and unconfined compressive strength. Furthermore, mineralogical analysis is carried out to predict brittleness based on the results of the XRD test, which produces mineral content in rocks. Brittleness analysis is very important for hydraulic fracturing stimulation planning, and to get a valid calculation result from BETRO-001 well log data which is dynamic data, it must be validated using static data, namely from uniaxial compressive tests on in-situ rock cores, but because of the difficulty of obtaining core data from BETRO-001 well drilling and other wells in the research location, a coring approach from analog outcrops is considered to represent the target formation. From the results of prospect criteria according to Matt McKeon (2013), it can be concluded that the Brown Shale Formation in Bengkalis Trough has good hydrocarbon shale potential and can be carried out for further research, because oil production from conventional Indonesian reservoirs in general has experienced a significant decline.